Hostile behaviours in children and adolescents: Sociodemographic and parental variables - Cruz, Carla (2020)
Abstract Background: Hostile behaviour in children and adolescents is a current and very relevant problem due to individual, social and economic harm it produces. Objectives: To verify if sociodemographic variables (gender, age, grade, place of residence and cohabitation) influence hostile behaviour in children and adolescents; to ascertain whether family variables (marital status, occupation, education level, monthly income) interfere with hostile behaviour in children and adolescents. Methodology: Quantitative, cross-sectional, descriptive and analytical study involving a sample of 999 students of the 2nd and 3rd cycles of basic education (5th – 9th years of schooling), with an average age of 12.15 years (SD=±1.46 years). Data collection includes the questionnaire of demographic data and family context, the Buss-Durkee Hostility Inventory. Results: Sociodemographic variables, sex, age, area of residence and cohabitation interfered in hostile behaviour in children and adolescents: girls, older students, residents in urban areas, living with parents were shown to have higher levels of hostile behaviours as a whole. Parents’ marital status, their secularity and family income also interfered in the hostile behaviour of the sample under study, finding that children and adolescents whose parents have no partner and have an average high / high household income reveal higher levels of hostile behaviours, particularly with regard to resentment, verbal hostility, fear, negativity and global hostility. Conclusion: We hope that this study contributes to preventing hostile behaviour in children and adolescents, reducing the potential risks of this problem.